Transformational school leadership and learning innovation for sustainable improvement of educational quality - Johan, Muhammad; Permana, Johar; Nurdin, Diding; Suryana, Asep (Indonesian Research Journal in Education |IRJE|, 2026)
This study investigates the relationship between transformational school leadership and learning innovation, as well as the sustainable improvement of educational quality. Using a quantitative design, data were collected from senior high school teachers through a structured questionnaire and analyzed with SmartPLS 4 using Partial Least Squares Structural Equation Modeling. The results show that transformational school leadership significantly enhances learning innovation, while learning innovation in turn significantly improves educational quality. In contrast, the direct effect of transformational school leadership on educational quality is positive but not significant. The mediation analysis confirms that learning innovation fully mediates this relationship. These findings suggest that school leadership contributes to educational quality when it is translated into practical innovation in learning materials, teaching methods, classroom culture, and assessment practices. The study recommends that principals strengthen instructional leadership, encourage teacher innovation, and build sustainable professional learning systems to support continuous improvement in educational quality.